H-infinity with Pole Placement Constraint in LMI Region for a Buck-converter Driven DC Motor - Mohd Zaidi, Mohd Tumari; Muhammad Salihin, Saealal; Mohd Riduwan, Ghazali; Yasmin, Abdul Wahab (IEEE, 2012)
This paper presents a modified Firefly Algorithm (MFA) for solving economics dispatch (ED) problems. ED is one of the most challenging problems of power system since it is difficult to determine the optimum generation scheduling to meet the particular load demand with the minimum fuel costs while all constraints are satisfied. In addition the practical ED problems which are involving objectives functions with quality and inequality constraints including the practical operations constraints of generators such as ramp rate limit, prohibited operating zones and generation limits make it harder to find the global optimum results of ED. To demonstrate the effectiveness and feasibility of MFA in solving ED, two well-known ED test systems with some of the most recently published ED solution methods in literatures. The results of this research show that MFA is able to find more economical solution than those determined by other methods.